EVALUASI KINERJA PELAKSANAAN TUGAS KEHUMASAN PADA INSTALASI HUMAS DAN PROMOSI KESEHATAN RUMAH SAKIT (PKRS) RSD DR SOEBANDI - Meilinda Rafika Sari; Sudarno Sudarno; Hendrawan Santosa Putra; Indah Purnamawati; Alfi Arif; Imam Mas'ud (VALUE: Journal of Business Studies, 2022)
The importance of public relations tasks in the hospital work system as a center for the formation of a brand image for the hospital towards the community is the main concern in determining the community's choice of hospital. Therefore, hospitals are required to carry out good public relations duties. The subject of this study was the Public Relations and PKRS Installation at RSD Dr Soebandi as one of the hospitals that has implemented and developed guidelines for the implementation of public relations tasks. The guidelines for the implementation of public relations tasks used by RSD dr Soebandi are compiled in the form of a Director's Decree. The research was conducted using in-depth interviews with informants to form the basis for formulating performance evaluations. The results showed that the Public Relations and PKRS Installation at RSD Dr Soebandi consisted of 3 units that jointly carried out public relations tasks, namely the PR and marketing unit, the PKRS unit, and the public complaints unit. After comparison, it was stated that the Public Relations and PKRS Installation of RSD dr Soebandi had not fully carried out their public relations duties in accordance with the agreed public relations task guidelines.